Factor structure of the bengali version of the fagerstrom test for nicotine dependence questionnaire: A cross-sectional study - Abhijit Dutta; Puja Bhakta; Anaitulah Ahmed Mir; Suman Singh; Athia Sylvia Saprunamei; Ramkripal Prajapati; Deepak Kumar Pandey; Ch Lily Anal; Nitin Saklani; Rachna Goenka; Subhas Singh; Abhijit Chattopadhyay; et al. (Indian Journal of Social Psychiatry, 2021)
Context: The Fagerstrom test for nicotine dependence (FTND) is a self-administered ordinal measure of nicotine dependence containing six items that evaluate the quantity of tobacco smoking, the compulsion to use, and dependence. Aims: To date, no Bengali version of the questionnaire is available. We aimed to develop its Bengali version and examine its cross-cultural adaptability considering linguistic equivalence. Settings and Design: A cross-sectional study was conducted through consecutive sampling at the outpatients of the National Institute of Homoeopathy, Kolkata. Subjects and Methods: The FTND-Bengali version (FTND-B) was produced by standardized forward-backward translations. The psychometric analysis was run to examine its factor structure, validity, and reliability. Reliability was examined using internal consistency (n = 263). Construct validity was examined by exploratory factor analysis (n = 132) using principal component analysis (varimax rotation). Subsequently, confirmatory factor analysis (CFA; n = 131) was performed to verify the model fit. Results: The internal consistency was acceptable (Cronbach's α = 0.701; 95% confidence interval [CI] 0.641–0.753). The Kaiser–Meyer-Olkin (=0.712) and Bartlett's test of sphericity (Chi-square 109.593, P < 0.001) both suggested adequacy of the sample. In factor analysis using varimax, all the items loaded above the pre-specified value of 0.3 and identified two components – “restraint” (question no. 1, 2, and 6) and “compulsion” (question no. 3, 4, and 5); explaining 56.1% of the variation. The goodness-of-fit in the CFA model was mediocre, but acceptable (Comparative Fit Index = 0.871, Tucker Lewis Index = 0.759, Root Mean Square Error of Approximation = 0.142, Standardized Root Mean Square Residual = 0.026). Conclusions: FTND-B, consisting of 6 items and framed within two components, appeared to be a valid and reliable questionnaire.